Strategi Pemasaran Klinik Telaga Indah Farma Batam dalam Meningkatkan Jumlah Kunjungan Pasien - Poppy Putri Pratiwi; Erliany Syaodih; Nining Handayani (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Health is the most important thing in life. Clinics play a role in increasing awareness of the importance of health and disease prevention measures. The type and quality of clinical services determines the superiority of the service which has an impact on the number of patient visits, however there has been a decline in the number of patient visits in the last few months. This condition is caused by several factors including internal factors and external factors, so an appropriate marketing strategy is needed to increase the number of patient visits. This research method is descriptive qualitative using SWOT analysis. Based on the results of this research, it shows that the clinic's marketing strategy is in quadrant III, namely by taking advantage of existing opportunities and developing internally. Marketing strategies include product strategy using system of products strategies, price strategy using economic strategies, place strategy with affordable access, promotion strategy using viral marketing strategies, physical evidence strategy using smart hospitals, people strategy by providing training, and process strategies using process focus strategy.